Molecular Identity and Location Influence Purkinje Cell Vulnerability in Autosomal-Recessive Spastic Ataxia of Charlevoix-Saguenay Mice - Toscano Márquez, Brenda; Cook, Anna A.; Rice, Max; Smileski, Alexia; Vieira-Lomasney, Kristen; Charron, François; McKinney, R. Anne; Watt, Alanna J. (Frontiers in Cellular Neuroscience, 2021)
Patterned cell death is a common feature of many neurodegenerative diseases In patients with autosomal-recessive spastic ataxia of the Charlevoix-Saguenay (ARSACS) and in mouse models of ARSACS, it has been observed that Purkinje cells in anterior cerebellar vermis are susceptible to degeneration and those in posterior vermis are resilient. Purkinje cells are known to express certain molecules in a highly stereotyped, patterned manner across the cerebellum. One such molecules is zebrin, which is expressed in a distinctive striped pattern. The different zones delineated by the expression pattern of zebrin and other patterned molecules have been implicated in the patterning of Purkinje cell death. We found that zebrin patterning appears normal prior to disease onset, suggesting that the development of zebrin-positive and -negative Purkinje cell zones occurred normally in Sacs−/− mice. Zebrin-negative Purkinje cells in anterior lobule III were preferentially susceptible to cell death, while anterior zebrin-positive cells and posterior zebrin-negative and -positive cells remained resilient even at late disease stages. The patterning of Purkinje cell innervation to the target neurons in the cerebellar nuclei showed a similar pattern of loss: neurons in the anterior region of the cerebellar nuclei, where inputs are predominantly zebrin-negative, were innervated by fewer zebrin-negative Purkinje cell puncta; whereas neurons in the posterior nuclei, whereas both zebrin-negative and zebrin-positive puncta appeared normal in the posterior region of the nuclei. These results suggest that both positional cues and molecular identity of Purkinje cells determine their susceptibility to cell death in ARSACS.